2005
DOI: 10.1073/pnas.0407146102
|View full text |Cite
|
Sign up to set email alerts
|

Release of long-range tertiary interactions potentiates aggregation of natively unstructured α-synuclein

Abstract: In idiopathic Parkinson's disease, intracytoplasmic neuronal inclusions (Lewy bodies) containing aggregates of the protein ␣-synuclein (␣S) are deposited in the pigmented nuclei of the brainstem. The mechanisms underlying the structural transition of innocuous, presumably natively unfolded, ␣S to neurotoxic forms are largely unknown. Using paramagnetic relaxation enhancement and NMR dipolar couplings, we show that monomeric ␣S assumes conformations that are stabilized by long-range interactions and act to inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

100
991
8
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 753 publications
(1,105 citation statements)
references
References 46 publications
100
991
8
6
Order By: Relevance
“…Observation of C-to-N terminal contacts in WT aS, 31,32 and data suggesting such contacts are abrogated in aggregation prone mutants 50 supported a proposed model in which long-range contacts prevented the formation of fibrilization pathway intermediates by occluding the hydrophobic NAC region of the protein. This model, however, was not supported by more recent studies of other synuclein family members, where the predicted correlation between long-range contacts and aggregation propensity was not observed.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Observation of C-to-N terminal contacts in WT aS, 31,32 and data suggesting such contacts are abrogated in aggregation prone mutants 50 supported a proposed model in which long-range contacts prevented the formation of fibrilization pathway intermediates by occluding the hydrophobic NAC region of the protein. This model, however, was not supported by more recent studies of other synuclein family members, where the predicted correlation between long-range contacts and aggregation propensity was not observed.…”
Section: Discussionmentioning
confidence: 69%
“…49 For aS, it has also been suggested that large amplitude RDCs in the C-terminal tail of the protein may report on long-range transient contacts between the C-terminus and regions in the N-terminal lipid-binding domain. 32 We measured RDCs for aS at pH 3.0 aligned in C8E5 bicelles and compared them to previous measurements at pH 7.4 43 (see Fig. 5).…”
Section: Residual Dipolar Couplingsmentioning
confidence: 94%
See 2 more Smart Citations
“…Intra-and intermolecular contacts can be detected in monomeric, unfolded αS and are implicated in modulating the aggregation propensity (Bertoncini et al, 2005;Dedmon et al, 2005;Outeiro et al, 2008;Wu and Baum, 2010). The negatively charged C-terminus remains disordered in several conformational states such as monomeric, fibrillar and membrane-bound αS (Del Mar et al, 2005;Eliezer et al, 2001;Qin et al, 2007;Ulmer et al, 2005;Vilar et al, 2008).…”
mentioning
confidence: 99%